2015
DOI: 10.1902/jop.2015.150166
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy With Sodium Alendronate for the Treatment of Experimental Periodontitis in Rats

Abstract: It can be concluded that topical use of SA as an adjuvant to SRP is effective in the treatment of experimental periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 51 publications
2
54
1
6
Order By: Relevance
“…The mechanical removal of dental plaque by SRP is the base of periodontal treatment, but may be flawed in some dental sites 2 . Thus, the aim of this study was to evaluate the local effects of statins as an adjuvant treatment to SRP in periodontal disease induced in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical removal of dental plaque by SRP is the base of periodontal treatment, but may be flawed in some dental sites 2 . Thus, the aim of this study was to evaluate the local effects of statins as an adjuvant treatment to SRP in periodontal disease induced in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease (PD) is a chronic infection produced by Gram-negative bacteria with high prevalence levels 2 . It occurs in gingiva in response to bacterial antigens of dental plaque, which accumulate along the gingival margin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hard tissue healing, it primarily inhibits the receptor activator of nuclear factor kappa B (RANK) signaling pathway and macrophage colony-stimulating factor (M-CSF) expression, leading to reduced osteoclast formation and bone resorptive capacity [30]. In soft tissue healing, it acts as a wound-healing enhancer with anti-inflammatory and antimicrobial biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…25,36 Previous studies have demonstrated the effects of systemic alendronate in human 37,38 and animal models 39,40 in decreasing loss and increasing density of alveolar bone. de Almeida et al 41 concluded that topical use of sodium alendronate as an adjuvant to scaling and root planing (SRP) shown to be effective in treatment of experimental periodontitis. Goes et al 42 found that alendronate prevented reduction of bone-specific alkaline phosphatase serum levels (BALP), alveolar bone loss and reduced inflammatory infiltrate, without causing systemic alterations.…”
Section: Use Of Bisphosphonates In Diagnosis and Management Of Periodmentioning
confidence: 99%